“A Wandering Existence”: Social Media Practices of Chinese Youth in the Context of Platform-Swinging - Hongxun Zhao; Jiahui Wang; Xurui Hu (Social Media + Society)
In the era of ubiquitous mobile internet, Chinese youth are engaging in dual pursuits of knowledge and employment through various social media platforms, showcasing unique social media practices. Via semi-structured interviews with 14 platform-swinging youth and NVivo12-assisted three-tier qualitative analysis, this study reveals the psychological mechanisms behind their “wandering” behavior. Spontaneous engagement, fulfillment of needs, resonance with peers, preservation of meaning, self-management, and intermittent swinging characterize youth’s complex wandering online activities. It further explores new dimensions of youths’ media practices, emphasizing subjective expression, identity reconstruction, boundary clarification, and visibility control. Moreover, wandering youth also encounter challenges like context collapse, losing their true selves, and self-pulling, which raises a critical question: Where will they wander?